Checklist and distribution of the family Notonectidae in Romania, with the first record of Notonecta maculata Fabricius, 1794 (Hemiptera: Heteroptera: Nepomorpha) - Berchi, Gavril Marius (Zootaxa, 2013)
Notonecta maculata Fabricius, 1794 is recorded for the first time from Romania. Five species belonging to the genus No-tonecta Linnaeus, 1758 and one to the genus Anisops Spinola, 1837 are now recorded from this country. The occurrence of Anisops sardeus sardeus Herrich-Schaeffer, 1849 and N. meridionalis Poisson, 1923 is confirmed by additional records. A checklist of the Notonectidae of Romania and updated distribution maps are provided.